Adrenomedullin induces pulmonary vasodilation but does not attenuate pulmonary hypertension in a sheep model of acute pulmonary embolism - Lagos-Carvajal, Angie Paola [UNESP]; Teixeira-Neto, Francisco José [UNESP]; Becerra-Velásquez, Diana Rocío [UNESP]; Diniz, Miriely Steim [UNESP]; Klein, Adriana Vieira [UNESP]; Rocha, Thalita Leone Alves [UNESP]; Dias-Junior, Carlos Alan [UNESP] (Elsevier B. V., 2015)
The pulmonary vasodilation induced by adrenomedullin may be beneficial in the acute pulmonary embolism (APE) setting. This study examined effects of adrenomedullin in sheep with microsphere-induced APE. Twenty four anesthetized, mechanically ventilated sheep were randomly assigned into 3 groups (n=8 per group): animals not subjected to any intervention (Sham), animals with APE induced by microspheres (500mg, intravenously) treated 30min later by intravenous physiological saline (Emb group) or intravenous adrenomedullin (50ng/kg/min) during 30min (Emb+Adm group). Plasma concentrations of cyclic adenosine (cAMP) and guanosine monophosphate (cGMP) were determined by enzyme immunoassay. Variables did not change over time in sham animals. In both embolized groups, microsphere injection significantly (P<0.05) increased pulmonary vascular resistance index (PVRI) and mean pulmonary artery pressure (MPAP) from baseline by 181% and 111-142%, respectively (% change in mean values). Adrenomedullin significantly decreased PVRI (18%-25%) and significantly increased cardiac index (22%-25%) from values recorded 30min after APE (E30), without modifying MPAP. Adrenomedullin decreased mean arterial pressure (18%-24%) and systemic vascular resistance index (32%-40%). Embolization significantly increased arterial-to-end tidal CO2 gradient, alveolar-to-arterial O2 gradient, and pulmonary shunt fraction from baseline, but these variables were unaffected by adrenomedullin. While adrenomedullin significantly increased plasma cAMP, cGMP levels were unaltered. Adrenomedullin induces systemic and pulmonary vasodilation, possibly via a cAMP mediated mechanism, without modifying the gas exchange impairment associated with APE. The pulmonary anti-hypertensive effect of adrenomedullin may be offset by increases in cardiac index.
Keywords: Adrenomedullin; Pulmonary embolism; Pulmonary hypertension